(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The field of Translation Studies has changed over the years by incorporating different methods, theories and practices. This work looks at modern problems in Translation Studies, especially with cultural aspects, technology, and changing approaches to translation. The project analyzes the contribution of translation studies to the problems and demonstrates that interdisciplinary approaches have much to offer. Moreover, it also addresses issues of machine translation and localization which brings new challenges and opportunities in terms of accuracy and quality. Globalization has increased the complexity surrounding intercultural communication, and, as a result, translators are expected to ‘manage’ linguistic, cultural and contextual factors adeptly. This paper contends that translation practice must be approached in a more flexible manner, taking advantage of technological advances while harnessing human knowledge for the best results in translation.